Moody Teachers Ruin My Motivation: An EFL Student's Voice on Effective EFL Teachers - Sri Rejeki Murtiningsih (Universitas Muhammadiyah Yogyakarta, 2017)
This focus of this study is to explore an English as a Foreign Language (EFL) student's perspectives on the characteristics of effective teachers that helped her develop her linguistic competence. This case study was conducted in an English education department in a private university in Indonesia. The data were obtained through two conversations with Aliyah, a third year EFL student. The analysis considered her learning experiences, reflection on her own learning, linguistic development, and factors influencing her linguistic development – all of which related to English. The findings show that reflecting from her past learning experiences, pedagogical and content knowledge are considered important characteristics of effective teachers. Most importantly, EFL teachers' personal traits, e.g. moody or knowledgeable were deemed to be a strong characteristic of effective EFL teachers as it influenced students' personal growths, such as motivation, attitude toward the course, and personal feelings. Implications of the study were also discussed.